Effectiveness of Digitalization and ESG Integration in Increasing the Relevance Value of Accounting Information - Ayu Lestari, Mey; Pratiwi, Nindya (Advances in Accounting Innovation, 2024)
Objective: The present research assesses the effects of digitalization and Environmental, Social, and Governance (ESG) practices on the applicability of accounting data, particularly Earnings Per Share (EPS) and Book Value Per Share (BVPS), in publicly traded companies in Indonesia.Methods: Using multiple regression analysis, the study tests the effects of ESG and digitalization on EPS and BVPS. Data is collected from Indonesian companies listed on the IDX for 2019-2023.Findings: The results indicate that while digitalization has a significant positive relationship with stock prices, ESG practices do not significantly enhance the relevance value of EPS and BVPS. ESG integration is found to weaken the relationship between accounting information and investor assessments. Additionally, the combined effect of digitalization and ESG on EPS and BVPS shows a negative correlation, suggesting that the current implementation of these practices does not effectively enhance the value relevance of accounting information.Novelty: This study provides new insights into the interaction between digitalization and ESG integration within the context of Indonesian companies. It highlights the challenges and inefficiencies in the implementation of these practices, offering a nuanced understanding of their impact on the value relevance of accounting information.Theory and Policy Implications: The results indicate that the current practices of ESG (Environmental, Social, and Governance) and digitalization may not be effectively improving the importance of accounting information. This emphasizes the necessity for consistent reporting and better execution